Penggunaan Laba dan Arus Kas untuk Memprediksi Kondisi Financial Distress: Studi Kasus pada Perusahaan Makanan dan Minuman yang Terdaftar di BEI Periode 2019-2022 - Riko Angguda, Windy; Blongkod, Harun; Mahmud, Mulyani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to examine the use of profits and cash flow in predicting financial distress conditions in food and beverage companies. This research uses quantitative descriptive analysis methods. Data was obtained from secondary data, namely data obtained from other parties in the form of published reports for the 2019-2022 period. The population of this research is all food and beverage companies listed on the Indonesian Stock Exchange. The number of samples in this research was 28 companies. The sampling method used was purposive sampling. The data was processed using Eviews 12. The results of this study show that profits have a significant effect on financial distress, while cash flow does not have a significant effect on financial distress in food and beverage companies listed on the Indonesia Stock Exchange. This research also states that profits and cash flow simultaneously influence financial distress.